Bacterium-Like Particles Displaying the Rift Valley Fever Virus Gn Head Protein Induces Efficacious Immune Responses in Immunized Mice - Zhang, Shengnan; Yan, Feihu; Liu, Dongping; Li, Entao; Feng, Na; Xu, Shengnan; Wang, Hualei; Gao, Yuwei; Yang, Songtao; Zhao, Yongkun; Xia, Xianzhu (Frontiers in Microbiology, 2022)
Rift Valley fever virus (RVFV), a mosquito-borne zoonotic phlebovirus, causes serious disease in humans and ruminants. According to the World Health Organization, Rift Valley fever is classified as priority disease, and as such vaccine development is of high priority due to the lack of licensed vaccines. In this study, a bacterium-like particle vaccine (BLP), RVFV-BLPs, was constructed. A novel display system was described, which is based on nonliving and non-genetically modified gram-positive bacterial cells, designated as gram-positive enhancer matrix (GEM). The RVFV Gn head protein was displayed on the surface of GEM by co-expression with the peptidoglycan-binding domain (protein anchor) at the C-terminus. We determined that the RVFV Gn head-PA fusion protein was successfully displayed on the GEM. Mice immunized with RVFV-BLPs produced humoral and cellular immunity. Interestingly, compared the production of RVFV Gn head-specific IgG and its subtype by vaccinating with different antigen doses of the RVFV-BLPs, which determined that the RVFV-BLPs (50μg) group showed a greater effect than the other two groups. More importantly, antibodies produced by mice immunized with RVFV-BLPs (50μg) exhibited potent neutralizing activity against RVFV pseudovirus. RVFV-BLPs (50μg) also could induce IFN-γ and IL-4 in immunized mice, these mice generated memory cells among the proliferating T cell population after immunization with RVFV-BLPs, with effector memory T cells as the major population, which means that RVFV-BLPs is an effective vaccine to establish a long-lived population of memory T cells. The finding suggest that the novel RVFV-BLPs subunit vaccine has potential to be considered a safe and effective candidate vaccine against RVFV infection.